The nursing interventions used at clinical practice in Brazil - Chianca, Tânia Couto Machado (2017)
There is a challenge in the world to standardize the nursing language and to give evidence to the nursing practice. Nursing Interventions Classification (NIC) is being developed by researchers of the College of Nursing - The University of Iowa, USA, with that purpose. The objective of this study was to identify the use of the NIC interventions in Brazil, through a survey of the 486 NIC interventions frequency of use by Brazilian nurses from several clinical specialties. A descriptive study carried out from March to July of 2006 with a sample of 222 Brazilian nurses was conducted. An instrument applied by the Iowa group of researchers was used for data collection. A statistic package was used for the data analysis. An agreement of 70% was considered acceptable and the central interventions considered used daily or weekly by the nurses were identified. The results showed that 77, 7% of the NIC interventions were identified as essential for the nurses of different specialties. The most frequent interventions show the essence of the nursing practice in Brazil and also the applicability of NIC interventions to our reality.